Effect of functional oils and algae on the performance of finishing pigs - Dendena, M. W.; Oliveira, R. R.; Cella, P. S. (Scientific Electronic Archives, 2016)
Abstract. The ban on the use of antibiotics as growth promoters because of the problems arising from this use, especially bacterial resistance and residues in animal products, he led the search for new alternatives that stood out the use of additives with natural components, who presented economically viable and beneficial. This work aimed to evaluate the effect of functional oils and algae on the weight gain of variables (WG), feed intake (FI), feed conversion (FC), feed cost per kilogram of animals produced and consistency of stool finishing pigs. Was used 18 animals distributed in a completely randomized design with two treatments (T1 - T2 and control treatment - Treatment with additives), three repetitions and three animals each. Performance data were submitted to analysis of variance, the difference between the averages verified by test F. The additive used is a mark consisting of castor oil, cashew nut oil, meal oyster shell, vermiculite and gender algae Spirulina.The daily feed intake was not affected by treatments (P> 0.05) and no significant differences were in fecal score of pigs. But the average daily gain and feed conversion were influenced significantly (P <0.05) by the treatments, and the additive treatment obtained the best results for both variables. It can be concluded that the use of functional oils and algae improved the productive and economic performance of pigs.